2020
DOI: 10.1002/sim.8490
|View full text |Cite
|
Sign up to set email alerts
|

A super‐combo‐drug test to detect adverse drug events and drug interactions from electronic health records in the era of polypharmacy

Abstract: Pharmacoinformatics research has experienced a great deal of successes in detecting drug‐induced adverse events (AEs) using large‐scale health record databases. In the era of polypharmacy, pharmacoinformatics faces many new challenges, and two significant challenges are to detect high‐order drug interactions and to handle strongly correlated drugs. In this article, we propose a super‐combo‐drug test (SupCD‐T) to address the aforementioned two challenges. SupCD‐T detects drug interactions by identifying optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Pharmacoinformatic studies have also identified ADE signals from longitudinal health data including electronic health record (EHR) data and administrative claims data. 15 , 16 , 17 Unlike SRS, EHR data and administrative claims data contain individual level and longitudinal information, including clinical outcomes (i.e., diagnoses) and medications (i.e., pharmacy prescriptions/claims). Compared to SRS, EHR data and administrative claims data contain more population groups (i.e., individuals without any ADE), variables (i.e., health conditions other than ADE), and detailed temporal information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacoinformatic studies have also identified ADE signals from longitudinal health data including electronic health record (EHR) data and administrative claims data. 15 , 16 , 17 Unlike SRS, EHR data and administrative claims data contain individual level and longitudinal information, including clinical outcomes (i.e., diagnoses) and medications (i.e., pharmacy prescriptions/claims). Compared to SRS, EHR data and administrative claims data contain more population groups (i.e., individuals without any ADE), variables (i.e., health conditions other than ADE), and detailed temporal information.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacoinformatic studies have also identified ADE signals from longitudinal health data including electronic health record (EHR) data and administrative claims data 15–17 . Unlike SRS, EHR data and administrative claims data contain individual level and longitudinal information, including clinical outcomes (i.e., diagnoses) and medications (i.e., pharmacy prescriptions/claims).…”
Section: Introductionmentioning
confidence: 99%